PENINGKATAN DAYA SERAP MATERI: SISTEM MULAZAMAH SEBAGAI SOLUSI PEMBELAJARAN SANTRI - Khoirun, Fuad Rizal; Ahmadi (LPPM STAI Muhammadiyah Probolinggo, 2024)
Learning is an obligation for every human being. Currently there are various learning methods used by various educational institutions. One of the learning methods used is what is called Mulazamah, which is the classic learning method of Salaf scholars. In this research we raised a theme around increasing the absorption capacity of material: the mulazamah system as a solution for student learning. The aim of this research is that it is hoped that it can provide an overview for many people so that they can add to their scientific knowledge. This qualitative method was chosen to provide an in-depth understanding and visuals of the implementation carried out. In the qualitative method, we as researchers will position ourselves as students, as well as society. Because basically testimony from experience and direct observation is needed in this discussion. In collecting data, participant interviews and literature study methods were used by studying data from various related references. This qualitative data analysis method was chosen because the data presented is in the form of interviews with participants, observation and documentation. Among the results of the research carried out was that the implementation of the mulazamah system was carried out by studying the books of the ulama, starting from adab, Arabic, fiqh and memorizing scientific texts. Keywords: Mulazamah; Sharia Science; PPTQ Ar Royyan.